Measurement invariance across countries of the Test of Memory Strategies (TMS): A contribution to the cross-national validity study - Giorgini, Roberto; Maestu, Fernando; Sara, Fernandes Margarida; Pastore, Massimiliano; Abellan, Maria; Quattrone, Andrea; Caparello, Sara; Quattrone, Aldo; Vaccaro, Maria Grazia (Acta psychologica, 2024)
Previous literature showed a complex interpretation of recall tasks due to the complex relationship between Executive Functions (EF) and Long Term Memory (M). The Test of Memory Strategies (TMS) could be useful for assessing this issue, because it evaluates EF and M simultaneously. This study aims to explore the validity of the TMS structure, comparing the models proposed by Vaccaro et al. (2022) and evaluating the measurement invariance according to three countries (Italy, Spain, and Portugal) through Confirmatory Factor Analysis (CFA). Four hundred thirty-one healthy subjects (Age mean = 54.84, sd = 20.43; Education mean = 8.85, sd =4.05; M = 177, F = 259) were recruited in three countries (Italy, Spain, and Portugal). Measurement invariance across three country groups was evaluated through Structural Equation modeling. Also, convergent and divergent validity were examined through the correlation between TMS and classical neuropsychological tests. CFA outcomes suggested that the best model was the three-dimensional model, in which list 1 and list2 reflect EF, list 3 reflects a mixed factor of EF and M (EFM) and list4 and list5 reflect M. This result is in line with the theory that TMS decreases EF components progressively. TMS was metric invariant to the country, but scalar invariance was not tenable. Finally, the factor scores of TMS showed convergent validity with the classical neuropsychological tests. The overall results support cross-validation of TMS in the three countries considered. •The assessment of Executive Functions and Memory separately could yield partial information about each involvement.•The Test of Memory Strategies (TMS) proposes to evaluate Memory and Executive Functions together.•The evaluation of factor structure and measurement invariance across groups is crucial to the validity appraisal of TMS.